The Influence of Price, Free Shipping, and Ease of Use on Purchase Decisions in the Tokopedia Marketplace (A Study on Tokopedia Marketplace Users in Bombana Regency) - lestari, Sri ayu; Wonua, Almansyah Rundu; Titing, Andry Stepahnie (Pascasarjana STIE Amkop Makassar, 2025)
This study examines the influence of price perception, free shipping promotions, and ease of use on consumer purchasing decisions in the Tokopedia marketplace, particularly among users in Bombana Regency, Indonesia. Utilizing a quantitative research approach with Structural Equation Modeling (SEM) based on Partial Least Squares (PLS), data were collected from 130 respondents through structured questionnaires. The findings reveal that price perception has the strongest influence on purchasing decisions (β = 0.514, p = 0.000), confirming that cost considerations remain the primary determinant in online consumer behavior. Free shipping promotions also exhibit a significant but weaker impact (β = 0.182, p = 0.002), suggesting that while promotional incentives reduce perceived transaction costs, their effectiveness depends on overall pricing strategies. Ease of use further contributes to purchase decisions (β = 0.258, p = 0.008), indicating that user-friendly platform features enhance consumer engagement but may not outweigh financial incentives. These findings underscore the importance of a holistic approach to e-commerce marketing, where pricing optimization, promotional strategies, and platform usability must be integrated to maximize consumer retention. Future research should explore additional behavioral and psychological factors, such as brand trust, customer service quality, and digital engagement patterns, to provide deeper insights into online consumer behavior. Keywords: Price Perception, Free Shipping Promotion, Ease Of Use, Purchase Decision, E-Commerce, Digital Marketplace